2020
DOI: 10.1177/0741088320939542
|View full text |Cite
|
Sign up to set email alerts
|

Are Two Voices Better Than One? Comparing Aspects of Text Quality and Authorial Voice in Paired and Independent L2 Writing

Abstract: Research has shown that collaboratively produced texts are better in quality compared with individually written texts. However, no study has considered the role of collaboration in authorial voice, which is an essential element in current writing curricula. This study analyzes the effects of collaborative task performance in the quality of L2 learners’ argumentative texts and in their authorial voice strength. A total of 306 upper-intermediate L2 learners were selected and divided into independent ( N = 130) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Not surprisingly, the finding about accuracy corroborates most recent studies on collaborative writing (Dobao, 2012 ; Elabdali, 2021 ; Shehadeh, 2011 ; Zabihi & Bayan, 2020 ) and WCF (Van Beuningen et al, 2012 ; Kurzer, 2018 ; Fukuta et al, 2019 ; Han, 2019 ; Lee, 2020 ; ; Sinha & Nassaji, 2021 ), thus further extending and establishing the positive roles of feedback and collaboration in promoting L2 writing development. Similarly, the finding about learners’ lack of development in complexity was also reported in the literature (Dobao, 2012 ; Sajedi, 2014 ; Storch, 2005 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Not surprisingly, the finding about accuracy corroborates most recent studies on collaborative writing (Dobao, 2012 ; Elabdali, 2021 ; Shehadeh, 2011 ; Zabihi & Bayan, 2020 ) and WCF (Van Beuningen et al, 2012 ; Kurzer, 2018 ; Fukuta et al, 2019 ; Han, 2019 ; Lee, 2020 ; ; Sinha & Nassaji, 2021 ), thus further extending and establishing the positive roles of feedback and collaboration in promoting L2 writing development. Similarly, the finding about learners’ lack of development in complexity was also reported in the literature (Dobao, 2012 ; Sajedi, 2014 ; Storch, 2005 ).…”
Section: Discussionsupporting
confidence: 86%
“…A meta-analysis of 33 studies suggests that collaboratively written texts were more accurate than individually written texts, with a mean effect size of a medium magnitude (g = 0.73) and that a large magnitude difference in rubric scores (g = 0.94) was found in favor of individual texts written after experimental CW conditions compared to those written after control individual writing conditions (Elabdali, 2021 ). For example, Zabihi and Bayan ( 2020 ) examined the effect of peer collaboration on an argumentative writing task in the CAF framework (complexity, accuracy, and fluency). Complexity was measured as the number of subordinate clauses to T-units, accuracy as the number of error-free T-units against the total number of T-units, and fluency as the average number of words per T-unit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Languaging manifests itself when learners get involved in completing communicative tasks through collaborative dialogues. Various studies (Kobayashi, 2003 ; Lapkin et al, 2002 ; Morris & Tarone, 2003 ; Storch, 1998 , 2004 ; Swain & Lapkin, 1998 ; Tin, 2003 ; Zabihi & Bayan, 2020 ; Zabihi & Ghahramanzadeh, 2022 ) have demonstrated that student collaboration, frequently referred to as small-group work, is of great significance in second language (L2) acquisition, social aspects of the classroom (i.e., how learners join together), and language pedagogy since working collaboratively enables learners to have a relatively better performance than working alone (e.g., Storch, 1999 ). One way for benefiting from collaboration is through a specific kind of interaction known as collective scaffolding (Donato, 1994 ), where learners can pool their cognitive and linguistic knowledge and work together to solve their language-related problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, an analysis of the rhetorical (e.g., rhetorical moves) and discoursal features (e.g., authorial voice, metadiscourse) in learners’ collaborative texts may provide valuable insights when relevant to the research goals and tasks. A handful of studies have attended to such aspects, including Li and Zhu (2017b) who analyzed the presence/absence of essential rhetorical elements in research proposals, Kuteeva (2011), who examined interactional metadiscourse (e.g., engagement markers, hedges, attitude markers) to understand the writer-reader relationship in wiki-based CW, and Zabihi and Bayan (2020), who studied multilingual learners’ authorial voice in collaborative argumentative writing tasks. For research that deems CW as a site for discourse co-construction and/or identity co-construction, the above-mentioned constructs provide additional perspectives to understand written products.…”
Section: Research Tasksmentioning
confidence: 99%